(untitled) (Innovative professional education, 2024)
Public-private partnerships (PPPs) in education: potentials and risks. The complexity of PPPs in education and their impact on accessibility, quality, and social justice are reflected upon. Various aspects of the influence of public-private partnerships in education are considered, emphasizing the necessity of careful regulation of PPPs to ensure the effectiveness and development of education.